Changes in Bovine Colostrum Metabolites during Early Postpartum Period Revealed by 1H-NMR Metabolomics Approach - S. Settachaimongkon; N. Wannakajeepiboon; P. Arunpunporn; W. Mekboonsonglarp; D. Makarapong (Tropical Animal Science Journal, 2021)
The objectives of this study were to characterize and compare non-volatile polar metabolite profiles of bovine colostrum, collected within 1 h and at 72 h after parturition, from crossbred Holstein cows raised in northeastern Thailand. The colostrum serum was characterized and compared using a non-targeted proton nuclear magnetic resonance (1H-NMR) technique combined with chemometric analysis. Results demonstrated that the main effect of post-parturition time provided a significant impact on the physical properties and major chemical constituents of colostrum, while the influence of farm origin and sampling month were likely undetectable. The 1H-NMR technique enabled to identify 45 non-volatile polar metabolites in the samples. Partial least-squares-discriminant analysis (PLS-DA) allowed discrimination of colostrum metabolome not only according to different times after parturition, but also the origins of the farm as well as sampling months. Differential metabolites were statistically identified as potential biomarkers accountable for the discrimination. Besides basic nutritive compounds (amino acids and sugars), several bioactive metabolites such as ascorbate, creatine, carnitine, choline, acetylcarnitine, N-acetylglucosamine, ornithine, orotate, and UPD-glucose could be successfully elucidated. Our finding reveals the application of non-targeted 1H-NMR metabolomics as an effective tool to assess the biomolecular profiles of bovine colostrum and their essential dynamics during the first three days after parturition.